2020
DOI: 10.34172/aim.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis and Neonates; Which Strategy?

Abstract: Background: Chorioamnionitis (CAM) is one of the major risk factors for neonatal early-onset sepsis (EOS). Different international guidelines have been developed for diagnosis and care of such neonates. This research aimed to evaluate our neonates and compare them with the guidelines. Methods: This prospective cohort study was conducted during five years (March 2012 to March 2017), and comprised of neonates (any gestational age) born to mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Nasal CPAP failure with APGAR score <3 in the first minute was 54.5%, APGAR score 4-7 was 37.5%, and APGAR score 7> was 10.5%. This result was different from the study conducted by Afjeh et al, 10 which showed 1-minute APGAR score was a predictor of CPAP failure in infants with very low birth weight and RDS. In our study, APGAR score was significantly related with CPAP failure based on bivariate analysis, but in multivariate analysis is did not proved to be a significant predictor of nasal CPAP failure.…”
Section: Discussioncontrasting
confidence: 99%
“…Nasal CPAP failure with APGAR score <3 in the first minute was 54.5%, APGAR score 4-7 was 37.5%, and APGAR score 7> was 10.5%. This result was different from the study conducted by Afjeh et al, 10 which showed 1-minute APGAR score was a predictor of CPAP failure in infants with very low birth weight and RDS. In our study, APGAR score was significantly related with CPAP failure based on bivariate analysis, but in multivariate analysis is did not proved to be a significant predictor of nasal CPAP failure.…”
Section: Discussioncontrasting
confidence: 99%
“…We enrolled 320 neonates, 172(53.8%) were male with a mean (SD) gestation age of 30.9 (2.95) weeks. The mothers mean age was 27 years, ranging (15–43). 70(22.4%) 95%CI:17.95,27.47] had IRS failure and 243(77.6%) had IRS success.…”
Section: Resultsmentioning
confidence: 99%
“…However, these findings were dissimilar to the study by Afjeh et al, where the noninvasive respiratory initial respiratory support (RA, oxygen via prongs, NCPAP/NIPPV) was successful in 147(41.7%) but failed in 175 (54.3%) neonates. (15). This could be attributed to a difference in study participants of VLBW neonates whereas our study had neonates ranging 575g to 2435g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might justify our clinical suspicion of CA even in the absence of a PIT of 38 0 C and more. In a recent prospective cohort study conducted by Sayyed AA et al among neonates exposed to suspected CA, 36% had PIT<37.8 0 C [ 42 ]. We observed that many of the mothers received intrapartum paracetamol if the temperature increased beyond 37.5 0 C, especially if it happened two or more times.…”
Section: Discussionmentioning
confidence: 99%